On a Version of the Spiritual Poem ‘Adam’s Lament’ - Рождественская, Милена (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper introduces the publication of and offers comments on ‘Adam’s Lament,’ a spiritual syllabic poem from an eighteenth-century manuscript preserved in the Library of Syktyvkar State University. The text has a number of compositional and ideological characteristics distinguishing it from the traditional ‘Adam’s Lament’ recorded in early Russian manuscripts dating from the second half of the 15th century or later. This syllabic verse is a notable example of the modern age religious folk poetry.